2018
DOI: 10.20858/tp.2017.12.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diagnosis Method for Checking the Wayside Systems for Wheel-Rail Vertical Load Measurement

Abstract: Nowadays, wayside measurement systems of wheel-rail contact forces have acquired great relevance for the monitoring of rolling stock, especially for freight trains. Thanks to these solutions, infrastructure managers can check and monitor the status of rolling stock and, when necessary, impose corrective actions for the railway companies. On the other hand, the evaluation of contact forces is part of the rolling stock authorisation process [1] and a mainstone for the study of the running stability. The data pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This kind of integration was almost absent, especially in the railway field. Only differential modelling allows accurate analysis of the wheel/ rail contact problem (in terms of contact forces, position and shape of the contact patch, stresses and strains), while multibody modelling is generally accepted as the current standard for studying railway dynamics [6].…”
Section: Science and Technologymentioning
confidence: 99%
“…This kind of integration was almost absent, especially in the railway field. Only differential modelling allows accurate analysis of the wheel/ rail contact problem (in terms of contact forces, position and shape of the contact patch, stresses and strains), while multibody modelling is generally accepted as the current standard for studying railway dynamics [6].…”
Section: Science and Technologymentioning
confidence: 99%
“…These sensors do not require significant modification to track components during the installation process. Over the past few decades, research on strain-gauge-based systems for track response monitoring has been noticeable ( 133 ). Although the use of strain-gauge-based systems for train-induced wheel-load measurement is relatively common, only a few studies have recently reported the use of these systems for rail–tie interaction force measurement ( 2, 5, 7, 9, 13, 14, 26, 27, 2933 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the system for measuring the vertical force acting in wheel/rail interaction is consists of two complexes of strain gauges installed on the rail neck at an angle of 45°symmetrically relative to the middle of the sleeper gap, where signals from eight strain gauges are summed [9,29,31,34,35]. With this system, we can measure the difference in displacement between two sections at some distance within the same spacing, and the actual position of the vertical load has not been considered in the results.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a constant measured value for several tens of centimeters is obtained, providing more reliable measurements [31]. Subsequently, the method of "piecewise-continuous" registration of vertical forces was improved by many researchers, for example, in [34,36,37]. The effective zone of the "piecewise-continuous" registration scheme in one inter-sleeper gap is approximately 0.2 m.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation